An Evaluation of a School-Based Savings Program and Its Effect on Sexual Risk Behaviors and Victimization Among Young Ghanaians. Issue 7 (October 2020) - Masa, Rainier; Chowa, Gina; Sherraden, Michael
The objective of this study was to examine the effect of a financial inclusion project on youth's sexual risk behaviors and victimization. The project occurred in Ghana, where 100 schools were assigned to either a school-based savings program (SBSP), a marketing campaign, or a control group. Pretest and posttest data were collected in 2011 and 2014, respectively. Given our study objective, we restricted our sample to sexually experienced youth ( n = 957). Using doubly robust methods to estimate treatment effects, the overall financial inclusion project was not associated with positive changes in sexual risk behaviors and victimization. In contrast, SBSP was significantly associated with higher likelihood of condom use and lower probability of sexual victimization. SBSP may be another promising tool that may help young people accumulate material and nonmaterial resources to reduce sexual risk taking and victimization.